2016
DOI: 10.3389/fevo.2016.00085
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Nutritional Acclimation of Sugar Maple (Acer saccharum Marsh.) and Red Maple (Acer rubrum L.) to Increasing Conifers and Soil Acidity as Demonstrated by Foliar Nutrient Balances

Abstract: Sugar maple (Acer saccharum Marshall, SM) is believed to be more sensitive to acidic and nutrient-poor soils associated with conifer-dominated stands than red maple (Acer rubrum L., RM). Greater foliar nutrient use efficiency (FNUE) of RM is likely the cause for this difference. In the context of climate change, this greater FNUE could be key in favoring northward migration of RM over SM. We used the concept of foliar nutrient balances to study the nutrition of SM and RM seedlings along an increasing gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
0
11
1
Order By: Relevance
“…In St. Hippolyte, Collin et al. () showed a similar foliar imbalance caused by a decrease in foliar Ca and Mg levels with the increasing presence of conifers and soil acidity. Also, while pH of the mineral soil was relatively similar between forest types, conifer‐dominated stands without maple regeneration distinguished themselves by having a significantly more acidic mineral soil (Table ).…”
Section: Discussionmentioning
confidence: 91%
“…In St. Hippolyte, Collin et al. () showed a similar foliar imbalance caused by a decrease in foliar Ca and Mg levels with the increasing presence of conifers and soil acidity. Also, while pH of the mineral soil was relatively similar between forest types, conifer‐dominated stands without maple regeneration distinguished themselves by having a significantly more acidic mineral soil (Table ).…”
Section: Discussionmentioning
confidence: 91%
“…The transition from the temperate to boreal forest, however, is particularly challenging for species that will need to cope with strong gradients in soil conditions and competition with boreal species. By investigating baseline conditions at migration sites as well as potential interspecific influences on species establishment, our study complements others examining site and/or biotic constraints to migration (Brown & Vellend, 2014;Carteron et al, 2020;Collin et al, 2016;Solarik et al, 2020). Site conditions are important because failure to establish at unsuitable sites will result in species distribution lagging behind suitable climate (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…Acer saccharum and A. rubrum show negative association across their range, implying spatial segregation, but were found to co-occur in up to 52% of migration sites. Field studies at the ecotone have shown that A. rubrum seedlings, more so than Acer saccharum, can tolerate low soil pH at sites where needle litter is abundant while also mobilizing nutrients from the soil better (Collin et al, 2016), characteristics that are important for breaking into the boreal forest. With time, A. rubrum could promote suitable soil conditions for a species like A. saccharum through increased pH and nutrient mineralization (Collin et al, 2016(Collin et al, , 2017 and/or the promotion of favourable soil biota (Brown & Vellend, 2014).…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…N deposition can cause deficiencies in other nutrients than N and nutrient imbalances due to a range of effects, including stimulation of plant growth (dilution effect) and negative effects on tree nutrient acquisition by modifying mycorrhizal associations 24,66 . Increasing mean annual temperature (MAT) also contributed to the decrease in Mg and the increase in Ca and N:P. Ca Moreover, in general, increases in soil pH translate into higher foliar cation concentrations [67][68][69] . The higher temperatures at the northern European sites favoured longer growing seasons, biological activity and nutrient up-take, thus accounting for the lower general decreases in foliar nutrient concentrations and even the increase in N. In contrast, the increases in temperature and consequently in drought (decreases in mean annual precipitation (MAP) in southern Europe could account for the decline in soil fertility and capacity of nutrient uptake, all of which contribute to a decrease in foliar nutrient concentration, as in experimental drought studies conducted in Mediterranean forests where mineralisation, soil enzymatic activity and plant growth also decreased, thus leading to a large decrease in aboveground nutrient mineralomasses 9,35,[70][71][72] .…”
Section: Discussionmentioning
confidence: 99%